Perioperative safety and short-term efficacy of functional minimally invasive esophagectomy. Issue 5 (May 2021) - Liu, Huibing; Jin, Defeng; Wang, Qian; Cui, Zhaoqing; Zhang, Luchang; Wei, Yutao
Background: Standard minimally invasive McKeown three-field esophagectomy (SMIE) results in high perioperative risk and poor postoperative quality of life owing to considerable surgical damage and numerous postoperative complications. We created a modified procedure, functional minimally invasive esophagectomy (FMIE), which preserves the azygos arch, bronchial artery, pulmonary branch of the vagus nerve, and the mediastinal pleura. Our aim was to evaluate the efficacy and safety of FMIE and to determine whether it has limited invasiveness. Methods: Between 2018 and 2020, FMIE was performed for 48 patients who were compared with 76 SMIE cases; 44 paired cases were matched using propensity score matching. Results: Operation time, extubation time, and postoperative hospital stay were significantly lower in the FMIE group. FMIE was also associated with fewer pulmonary infections. Postoperative drainage volume on postoperative day (POD) 1 and POD 2, and white blood cell counts on POD 2 and POD 4 were also significantly lower in the FMIE group. There was no statistically significant difference in the number of dissected lymph nodes, short-term recurrence, metastasis rates, or survival rate between the two groups. Conclusions: FMIE is a less invasive procedure and may be a suitable alternative for lower and early middle esophageal carcinoma.